Report of the Working Group on Urban Development - Planning and Implementation - Planning Commission (Planning Commission, 1981)
The Report on Urban Development Planning and Implementation examines the challenges posed by rapid urbanization in India and proposes a comprehensive framework for sustainable urban growth. Prepared by the Working Group constituted by the Planning Commission in 1972, the report highlights the accelerating pace of urban population growth, inadequacies in infrastructure, and the absence of an integrated national urban policy. It critiques existing planning methodologies and recommends a two-tier administrative structure to improve coordination between regional planning authorities and municipal bodies. Emphasis is placed on integrated financing mechanisms, enhanced central government participation, increased public land ownership, and capacity building through specialized training. The report underscores the need for higher development outlays and coordinated policy efforts to improve urban living conditions and support balanced socio-economic development.
Planning Commission New Delhi
Planning Commission New Delhi
Keywords: rban Development Planning; Planning Commission of India; Urbanization in India; National Urban Policy; Urban Infrastructure; Municipal Authorities; Planning and Development Authorities; Integrated Urban Financing; Urban Governance Framework; Resource Mobilization; Capacity Building; Metropolitan Development